PENERAPAN STRATEGI INKUIRI UNTUK MENINGKATKAN PENGUASAAN KONSEP GETARAN DAN GELOMBANG - Sixtus Iwan Umboh (Charm Sains: Jurnal Pendidikan Fisika, 2020)
Research on the application of incuiri strategis for improve mastery of the conceps of vibration and waves.The purpose of the study is 1) Knowing the relationship of mastery of the initial concept with the result of learning to study physics students junior high school Savio Dominiko Manado on matter of vibration and waves.2) To Determine the effectiviness of applying inquiri learning strategies in vibration and wave material. The physic material used is vibration and waves. This study used the experimental method Pre-test and Post-test control group design. The research subyek taken in this study were the 8 th grade students of Catholic high school Savio Dominiko Manado with a total of 22 students. Data collection was carried out by holding a Pre-test and Post-test to find out the mastery of the conceps of vibration and waves. Data is processed using t test statistic. The results of the study show 1) there is a positive and significant relationship between mastery of the initial concept and achievement of student learning outcomes on vibration and wave material seen t count = 2,196 while t table =20,18. 2) Student group learning outcomes taught with conventional learning strategies that can be seen from average value of achievement for the control class is 70,0 and also seen from t count t count t table that is obtained t count = 1,975 while t table = 1,721